Exegeting The Qur’an in Friday Sermons: Characteristics of Oral Interpretation by Preachers at Taqwa Mosque, Langsa, Aceh - Ramadhani, Wali; bin Mohd Saad, Mohd Faizulamri; Humaira, Dara (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This article examines the characteristics of oral interpretation of the Qur’an by Friday preachers at Taqwa Mosque in Langsa Aceh. The oral interpretation in Friday sermons is compelling subject for study because the preachers elucidated Qur’anic verses during their discourse. These preachers convey religious messages grounded in the hadith and Qur’anic texts, which were interpreted contextually. This study employs qualitative methodology, incorporating phenomenological and hermeneutical approaches. The collected data were analyzed using Gadamer’s hermeneutic theory and Walter J. Ong’s theory of orality. The findings of this research, grounded in these theoretical frameworks, reveal two primary results. First, the Friday preachers’ interpretations of the Qur’an are deeply influenced by their preexisting understandings. Second, the oral interpretation in their Friday sermons exibit characteristics that are additive, aggregative, redundant, conservative, closely tied to human lifeworld, agonistic, empathic-participative, homeostatic, and situational.